Enterprise Resource Planning (ERP) Design Using TOGAF ADM and ACMM (Case Study: PT XYZ) - Triyanto, Triyanto; Supriyanto, Aji (Information Technology International Journal, 2024)
Enterprise Resource Planning (ERP) is software used by companies to unite and manage information from various parts of the company, or a tool that integrates all aspects of business in a company. However, in order to support the operations of PT XYZ, it has not implemented an Information System in its business activities. In order to support the smooth running of business processes at PT XYZ, it is necessary to design a structured Information System with good planning using the TOGAF ADM framework. Before starting the design, the researcher evaluated the maturity level of PT XYZ by comparing the current condition with the desired one using the Architecture Capability Maturity Model (ACMM). The results of this evaluation were recommendations for an ERP architecture that was adapted to PT XYZ's business processes, including business architecture, data, applications, and technology that have reached their respective level 3 maturity levels.